PERUBAHAN PERILAKU KONSUMEN RUMAH TANGGA DI JAWA BARAT DALAM PEMBELIAN SEMBAKO PADA MASA PANDEMI COVID-19 - Suhanda, Aludra Septariza; Kurnia, Ganjar (Universitas Galuh, 2023)
The COVID-19 pandemic has suppressed all aspects of life, but opportunities have opened up in the economic sector, namely the increase in the use of e-commerce. West Java is the province that has the highest e-commerce transactions. The food ingredient category, which generally includes basic necessities, is the most widely sold e-commerce business in West Java. The purpose of this study describes the factors related to changes in consumer behavior in purchasing basic necessities during the pandemic. The research method used is quantitative with a survey approach. The study was conducted on household consumers in West Java. The results showed that: (1) the majority of consumers are aware of online food purchases, (2) the possibility of trying is the innovation characteristic most related to decision making in adopting online staple food purchases, (3) there has been a change in online food purchase decision making during and after the COVID-19 pandemic but the changes are not too large, (4) consumers who have made the decision to adopt online staple food purchases continue to Implementation stage, (5) the majority of consumers do not find problems in purchasing basic necessities online, so consumers tend to continue purchasing basic necessities online after the COVID-19 pandemic.